Influence of soaking Malus domeri (Bois) Chev. leaves on gut microbiota and metabolites of long-living elderly individuals in Hezhou city, Guangxi, China - Hui Nie; Zhongyang Gao; Yanghe Luo; Yajuan Wang; Feiyang Wu; Guangqing Mu; Xiaomeng Wu (Food Science and Human Wellness)
To investigate the effects of drinking the soaking of Malus domeri (Bois) Chev. leaves on gut microbiota and metabolites of long-living elderly individuals in Hezhou city, Guangxi, China. It has been reported that longevity is closely related to metabolism and the gut microbiota. The 16S rRNA sequencing and liquid chromatography-mass spectrometry (LC-MS) were used to analysis fecal samples and explore the factors affecting longevity in the region. Interestingly, we discovered, that elderly individuals who had been drinking the soaking of M. domeri (Bois) Chev. leaves for a long time exhibited higher diversity of the gut microbiota than without drinking the soaking, notably. The proportions of Ruminococcaceae and Prevotella were decreased in those who did not drink this soaking. In addition, a total of 106 metabolites were characterized, and the people of long-lived people (> 90 years old) and elderly people (< 90 years old) who drinking soaking of M. domeri (Bois) Chev. leaves signif icantly altered the gut microbiota and upregulate d levels of haplopine, farnesol, genipic acid, momordicinin, 2-hydroxyestrone, hydroxyphenyllactic acid, caffeic acid, sophoraflavanone B, and soyasaponin I. We preliminarily determined that M. domeri (Bois) Chev. leaves consumption may be an important factor affecting longevity in this area.